Advances in nursing care for post-stroke limb dysfunction rehabilitation - Bai, Jie; Chen, Kecheng (Frontiers in Neurology, 2025)
Stroke-induced limb dysfunction has a significant impact on patients’ functional independence and quality of life. While rehabilitation efficacy depends largely on patient motivation, psychological factors often impede treatment adherence and functional recovery. This narrative review synthesizes current evidence on psychological factors affecting rehabilitation motivation, assessment tools, and evidence-based interventions for stroke patients with limb dysfunction. Psychological barriers, including kinesiophobia, diminished self-efficacy, perceived burden, and inadequate social support, significantly predict rehabilitation outcomes. Clinically validated assessment tools demonstrate variable utility across recovery phases, with the Pittsburgh Rehabilitation Participation Scale offering efficiency in acute settings and the Motivation in Stroke Patients for Rehabilitation Scale providing comprehensive evaluation during subacute and chronic phases. Evidence supports multimodal intervention strategies that combine psychological approaches (such as motivational interviewing) with technological innovations (virtual reality, game-based therapy, wearable devices). Clinical implementation should prioritize early psychological screening within 72 h of admission, followed by integrated assessment protocols combining clinician-rated and self-report measures. Furthermore, personalized motivation enhancement protocols tailored to patients’ cognitive status and recovery phase, along with robust interdisciplinary collaboration between rehabilitation nurses, physical therapists, and psychologists, are essential. Ultimately, this integrated approach optimizes rehabilitation outcomes by comprehensively addressing both physical and psychological dimensions of stroke recovery. In the future, studies should emphasize multidimensional analyses that incorporate individual patient characteristics to develop precise rehabilitation interventions, thereby proposing new strategies for optimizing functional recovery in stroke survivors.